Prevalence of Congenital Hypothyroidism and G6PD Deficiency in Newborns in a Tertiary Care Hospital of Central India. Issue 1 (March 2021) - Patel, Suprava; Priya, Ritu; Padhi, Phalguni; Naik, Tripty; Abraham, Jessy; Nanda, Rachita; Mohapatra, Eli; Agrawal, Sarita
Objectives: The fundamental prerequisite of a screening program is the accessible epidemiological data regarding disease burden and awareness regarding the disorder. This is the foremost study in this state to estimate the burden of congenital hypothyroidism (CH) and glucose-6-phosphate dehydrogenase (G6PD) enzyme deficiency in infants born or attending a tertiary care hospital, pursuing skill development for the technical staffs, and creating awareness for parents. Study Design: A cross-sectional study for 21 months was conducted in the Department of Biochemistry in collaboration with the Department of Pediatrics and Department of Obstetrics and Gynecology. Methods: The screening was conducted on 1282 babies, 48 hours subsequent to birth and up to 8 weeks of age. The dried blood spot specimens collected were analyzed for thyroid stimulating hormone (TSH) level and G6PD enzyme activity by fluoroimmunoassay method. Prevalence was calculated by percentage. Results: The proficiency of the program for all live birth babies delivered in the institute was 94.6%. In consequence to improper sampling, 4.1% samples could not be analyzed. The screening tests reported elevated TSH levels in 1.6% of total population and G6PD enzyme deficiency in 2.6% of all babies enrolled. Confirmatory tests revealed that 4 (3.1/1000) babies were declared positive for CH and 8 (6.2/1000) were announced to be G6PD deficient. Conclusion: The new prevalence observed is one of the highest prevalence of CH published in India that urges mandatory and immediate need for development of newborn screening program in the state, and improvisation and upgradation of regional diagnostic center with facilities for primary- and secondary-level testing.